The Role of Investment Opportunity Set Between Profitability and Debt Policy - Mahrita, Ani; Fadli, Jul Aidil (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2026)
This study aims to examine the effect of profitability on debt policy with the Investment Opportunity Set (IOS) as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The mining sector was selected due to its capital-intensive characteristics and high investment requirements, which make financing decisions particularly crucial. This research employs a quantitative approach using secondary data derived from companies’ financial statements. The sampling technique used is purposive sampling, resulting in 34 companies that meet the specified criteria. Data analysis is conducted using multiple regression and Moderated Regression Analysis (MRA) with the assistance of IBM SPSS version 27. The findings indicate that profitability has a significant negative effect on debt policy, suggesting that companies with higher profitability tend to rely more on internal financing rather than external debt. This result is consistent with the Pecking Order Theory, which posits that firms prioritize internal funds over external financing sources. Furthermore, the analysis reveals that the Investment Opportunity Set is unable to moderate the relationship between profitability and debt policy. This implies that the availability of investment opportunities does not strengthen or weaken the influence of profitability on corporate debt decisions. These findings highlight that, despite the large investment potential in the mining sector, companies prefer to utilize retained earnings when profitability is high, thereby reducing dependence on debt financing. The inability of IOS to act as a moderating variable suggests that other factors, such as firm size, growth opportunities, or dividend policy, may play a more significant role in influencing debt policy. This study contributes to the financial management literature by providing empirical evidence on capital structure decisions in emerging markets, particularly in Indonesia’s mining industry..